1971
DOI: 10.1113/jphysiol.1971.sp009391
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic regulation of hepatic tyrosine transaminase activity

Abstract: SUMMARY1. The cholinergic agent carbachol (0.5 mg/kg) produces within 2 hr a two-to threefold increase in the activity of hepatic tyrosine transaminase in the adrenalectomized fasted rat.2. The carbachol-evoked rise in enzyme activity is prevented by pretreatment with atropine.3. Cycloheximide, an inhibitor of protein synthesis, prevents the carbachol-evoked rise of enzyme activity; actinomycin D, an inhibitor of RNA synthesis, partially reduces it. 4. Atropine or unilateral (right or left) vagotomy suppresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1973
1973
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…These results suggest that the hypothalamic cholinergic influence on liver tyrosine aminotransferase is mediated largely by the cholinergic system in the LH-vagal pathway. Our results are consistent with the view of Black and Reis [62] that the vagal-cholinergic nerves are concerned in neural regulation of liver tyrosine aminotransferase.…”
Section: Hypothalamo-hepatic Relation In the Control Of Amino Acid Mesupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that the hypothalamic cholinergic influence on liver tyrosine aminotransferase is mediated largely by the cholinergic system in the LH-vagal pathway. Our results are consistent with the view of Black and Reis [62] that the vagal-cholinergic nerves are concerned in neural regulation of liver tyrosine aminotransferase.…”
Section: Hypothalamo-hepatic Relation In the Control Of Amino Acid Mesupporting
confidence: 93%
“…Black and Reis [62] showed that electrical stimulation of the vagus nerves or" administration of carbachol in adrenalectomized rats induces the activity of liver tyrosine aminotransferase (EC 2.6.1.5), an enzyme catalyzing the first reaction in the pathway by which tyrosine is finally degraded to acetoacetate and fumarate. As an extension of our previous studies [11][12][13][14] on chemical coding of the hypothalamic neurones in metabolic control, we have investigated the hypothalamic control of this hepatic enzyme by selectively stimulating the LH, a presumed parasympathetic centre [2,5,6], with different neurotransmitters.…”
Section: Hypothalamo-hepatic Relation In the Control Of Amino Acid Mementioning
confidence: 99%
“…There is some evidence that the autonomic nervous systems regulate enzyme synthesis, as reported for the appearance of circadian rhythmic changes in phosphoenolpyruvate carboxykinase in the liver of fed rats (27) and induction of tyrosine transaminase in rat liver (18). Moreover, alkaline phosphatase in rat atria has been reported to be induced by subcutaneous injection of isoprenaline (28).…”
Section: Discussionmentioning
confidence: 93%
“…Especially, bilateral cervical vagotomies significantly suppress DNA synthesis in partially hepatectomized liver [14]. Cch also affects various liver metabolisms, such as biosynthesis of cholesterol [18], hepatic tyrosine aminotransferase [19], tyrosine transaminase [20], glycogen formation, and the activities of glycogen synthetase [21], phosphoenolpyruvate carboxykinase [22], glucokinase [22], and ornithine decarboxylase [14]. However, it is still obscure whether the Cch induces hepatocyte proliferation.…”
mentioning
confidence: 99%